2017
DOI: 10.7150/ntno.19158
|View full text |Cite
|
Sign up to set email alerts
|

Improving Brain Delivery of Biomolecules via BBB Modulation in Mouse and Rat: Detection using MRI, NIRF, and Mass Spectrometry

Abstract: There is an urgent need to develop new and alternative methods to deliver functional biomolecules to the brain for diagnosis and treatment of brain diseases. The goal of this study was to evaluate the activity of blood-brain barrier (BBB) modulators (i.e., HAV and ADT peptides) to deliver functional biomolecules (i.e., galbumin, IRdye800cw-cLABL, and cIBR7) to the brains of mice and rats. HAV6, cHAVc3, and ADTC5 peptides but not HAV4 peptide significantly enhanced the brain delivery of 65 kDa galbumin compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Assessing transport of nanoparticles, proteins, and other therapeutics across the BBB can be challenging; nonetheless, researchers have designed various in vivo models to investigate this transport in both heathy and diseased BBB . Animal models inherently include all contributing factors that dictate the transport across the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing transport of nanoparticles, proteins, and other therapeutics across the BBB can be challenging; nonetheless, researchers have designed various in vivo models to investigate this transport in both heathy and diseased BBB . Animal models inherently include all contributing factors that dictate the transport across the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that ADTC5 allowed the BBB permeation of a small molecule such as gadopentetic acid (Gd-DTPA; MW = 547.6 Da) in a time window of 0 to 2 h; however, no molecules could pass through the BBB after 4-h. 64 This indicates that the pores created by ADTC5 to allow gadopentetic acid to cross the BBB were closed between 2 to 4 h. In contrast, ADTC5 allowed only 65 kDa galbumin to enter the brain after 10-min delay, but no albumin could cross the BBB after 40-min delay. 27 Thus, for a large molecule such as galbumin, the pores closed between 10 to 40 min. Finally, a 20-min delay between administrations of ADTC5 and IgG mAb did not allow the penetration of IgG mAb across the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…Linear and cyclic cadherin peptides as BBBM (e.g., HAV6, Ac-SHAVSS-NH2; ADTC5, Cyclo(1,7)Ac-CDTPPVC-NH2) have been shown to improve brain depositions of various sizes of proteins (e.g., 15 kDa lysozyme, 65 kDa albumin, 150 kDa IgG mAb) in C57BL/6 mice. [25][26][27] A combination HAV6 peptide and anticancer drug adenanthin has been shown to effectively suppress brain tumor growth and enhance animal survival in the mouse model of medulloblastoma brain tumor. 28 Recently, multiple treatments of experimental autoimmune encephalomyelitis (EAE) mice (an animal model of multiple sclerosis (MS)) with a combination of ADTC5 and BDNF significantly suppressed disease relapse compared to those treated with BDNF alone, ADTC5 alone, and PBS.…”
Section: Introduction and Epidemiologymentioning
confidence: 99%
“…Ulapane et al reported that a cyclic ADT peptide, ADTC5, enhances the delivery of functional molecules, such as 65 kDa galbumin and peptides (e.g., cIBR7), creating a short opening (longer than 10 min but shorter than 40 min) of the BBB in mouse and rat models. They also conclude that BBB modulation by cadherin peptides depends on different factors, such as the type and dose of modulator peptide, the timing of delivery between BBB modulator and the delivered molecule, and the size of the delivered molecules [ 90 ]. Another interesting study was conducted by Laksitorini et al using different cyclic ADT peptides (ADTC1, ADTC5, ADTC6).…”
Section: Bbb Pharmacological Modulation For Treatment Of Human Glimentioning
confidence: 99%